Spillover and mobility of species on solid surfaces - Guerrero-Ruiz, A.; Rodriguez-Ramos, I. (Studies in surface science and catalysis, 2001)
"Spillover and Mobility of Species and Solid Surfaces" collects the papers which were presented at the Fifth International Conference Spillover, either as oral or poster contributions, as well as the summaries of the invited lectures. This congress and its publication in the Studies on Surface Science and Catalysis series follow the tradition of previous conferences on spillover, initiated in Lyon, 1983, and continued in Leipzig, 1989, Kyoto 1993 and Dalian, 1997. For the fifth conference, held in S.L. el Escorial (Madrid), the organising committee has attempted to compile representative contributions which illustrate the advances in understanding the spillover phenomenon since 1997. Spillover is a process taking place during the interface of gas reactant molecules (mainly hydrogen and oxygen) on solid surfaces. However, different contributions to the more general area of the chemistry at surfaces, related with the mobility and migration of species, diffusion through membranes, fuel cell catalysts, etc., have also been included. In fact the title of the present volume summarizes this attempt to extend the conference topics towards dynamics at surfaces. Among the 70 contributions received, the 56 accepted papers were selected on the basis of the reports of at least two international reviewers, according to standards comparable to those applied for other specialised journals. These papers are from 21 different countries.